Management of cleft lip and palate in Nigeria: a survey (2018)
Background: Clefts of the lip and/or palate are the most common congenital craniofacial defects and second only to club foot among all congenital anomalies. The management of this condition is resource intensive due to the multidimensional needs. This survey was carried out to ascertain the current state of cleft management in Nigeria with emphasis on training, scope of management, and assessment of treatment outcome. Materials and Methods: Structured questionnaires were administered to cleft surgeons based on professional and practitioners’ register and the result of literature search for cleft surgeons whose names may not appear in the registers. Results: A total of 69 returned questionnaires were analyzed. The highest number of surgeons was from southwest geopolitical region while the northeast had the least. Fifty-eight (84.1%) were specialists with the fellowships. Forty-seven had been cleft surgeons for <10 years. Majority undertook lip repair between 3 and 4 months while 50% did cleft palate at or more than 9 months. Millard rotation and advancement was used for lip repair by 91.2% and 44 employed the von Langenbeck technique for palatal repair. Forty-six respondents carried out nasal repair at the time of lip surgery with 44 doing this as closed rhinoplasty. Adhesive tapes were usually employed by 44 (63.7%) for managing the protruding premaxilla. Orthodontic evaluation was not usually part of the treatment plan of 34 respondents. Otology assessment and assessment of velopharyngeal competence were rarely done. Revision surgeries, alveolar bone grafting, rhinoplasties, and maxillary osteotomies were uncommon. Interdisciplinary team care approach was practiced by 54 (78.2%) respondents. Conclusion: Findings suggest an increase in the number of surgeons, but the training, scope, and standard of care remain relatively limited. Audit and assessment of the practice should also become points of emphasis.